2021
DOI: 10.1002/ijc.33686
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of tumor cell entry of aloe‐emodin, a natural compound endowed with anticancer activity

Abstract: Aloe-emodin (1,8-dihydroxy-3-[hydroxymethyl]-anthraquinone), AE, is one of the active constituents of a number of plant species used in traditional medicine. We have previously identified, for the first time, AE as a new antitumor agent and shown that its selective in vitro and in vivo killing of neuroblastoma cells was promoted by a cell-specific drug uptake process. However, the molecular mechanism underlying the cell entry of AE has remained elusive as yet. In this report, we show that AE enters tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Kaempferide has shown promising effects on HCC and other cancers (Chandrababu et al, 2023). Purpurin (Singh et al, 2021) and aloe-emodin (Ahirwar, 2011; Pecere, 2021; Semwal, 2021) are anthraquinones that have reported anticancer properties. Coumarin (Kumar et al, 2018), cynidin 3 glucogalactoside (Chen et al, 2020), palmitic acid (Harada et al, 2002), and piperidine (Rashmi Wardhan et al, 2020; Reshmi et al, 2010) present in HMK have shown activity against lung, breast, leukemia, and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferide has shown promising effects on HCC and other cancers (Chandrababu et al, 2023). Purpurin (Singh et al, 2021) and aloe-emodin (Ahirwar, 2011; Pecere, 2021; Semwal, 2021) are anthraquinones that have reported anticancer properties. Coumarin (Kumar et al, 2018), cynidin 3 glucogalactoside (Chen et al, 2020), palmitic acid (Harada et al, 2002), and piperidine (Rashmi Wardhan et al, 2020; Reshmi et al, 2010) present in HMK have shown activity against lung, breast, leukemia, and other cancers.…”
Section: Discussionmentioning
confidence: 99%